P2X7 1513 A>C Polymorphism Confers Increased Risk of Extrapulmonary Tuberculosis: A Meta-analysis of Case-Control Studies - Y. Areeshi, Mohammed; K. Mandal, Raju; Dar, Sajad; Wahid, Mohd.; Ekhlaque A. Khan, Md.; K. Panda, Aditya; Jawed, Arshad; Haque, Shafiul (Current Genomics, 2016)
The association of A1513C (rs3751143) polymorphism of P2X7 gene with the risk of extrapulmonary tuberculosis (EPTB) has been extensively analyzed, but no consensus has been achieved. In this study, a meta-analysis was done to assess this precise association. Online web databases, like PubMed (MEDLINE) and EMBASE were searched for pertinent reports showing association of P2X7 A1513C polymorphism with EPTB risk. To assess the strength of this association, we calculated pooled odds ratios (ORs) and 95% confidence intervals (95% CIs). A total of eight reports involving 2237controls and 594 EPTB cases were included in this study. Four genetic models, viz. allele (C vs. A: p=0.011; OR= 1.677, 95% CI = 1.125–2.501), homozygous (CC vs. AA: p = 0.053; OR= 2.362, 95% CI = 0.991–5.632), heterozygous (AC vs. AA: p = 0.003; OR= 1.775, 95% CI = 1.209–2.607) and dominant (CC + AC vs. AA: p = 0.005; OR= 1.890, 95% CI = 1.207–2.962) showed significant associations compared with wild type genotypes. Subgroup analysis stratified by ethnicity was also performed and the results suggested that homozygous and heterozygous genotypes were associated significantly with increased susceptibility of EPTB in Asian population. Similarly, heterozygous and dominant models showed increased EPTB risk in Caucasian population. The present meta-analysis suggests that P2X7 A1513C polymorphism may be an important risk factor for EPTB. Also, our sub-group analysis indicates that P2X7 A1513C polymorphism confers increased EPTB risk among Asians and Caucasians. However, future larger studies are needed to provide more precise conclusion and endorse the present results.
Keywords: meta-analysis